A Prayer to Horus Praising Edfu - Gabler, Kathrin (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
The article publishes a hieratic ostracon from the Ramesside Period, now stored in the magazine of the Ministry of Tourism and Antiquities at Elkab and probably found in (Hagr) Edfu. The text is a prayer to Horus and belongs to the literary genre known as the ‘praises of cities’. The first lines present a close parallel to Ostracon Nakhtmin 87/173, obverse, ll. 1–2, found in Theban Tomb 87; that ostracon bears a prayer to Amun and dates back to Dynasty 18. A comparison of both versions shows how easily such poems could be adapted and how the texts were passed on to later generations. On the Edfu ostracon, the copying work involved either a memory slip or perhaps a deliberate pun.